Upaya Meningkatkan Kompetensi Guru Bahasa dalam Menulis Buku Fiksi melalui Bimbingan Kelompok di MTs Negeri 6 Kulon Progo - Barokatussolihah (Jurnal Pendidikan Madrasah, 2022)
This research aims to find out the application of group guidance as an effort to improve the competence of language teachers in writing fiction books in MTs Negeri 6 Kulon Progo. This research uses academic supervision techniques through group guidance. Based on the results of guidance, it can be concluded that there is an increase in the competence of language teachers in writing fiction books by 95%. As a result of the data group's guidance, there were 7 language teachers who wrote books both single and anthology along with offline or online guidance. Overall, this best practice activity has succeeded in improving the literacy skills of language teachers through group guidance.